Molding material
By optimizing the molecular weight distribution of the resin in the molding materials and adding cellulose fibers, polyester-based elastomers and high-polar polyesters, the problem of mechanical strength reduction under the history of molding heat is solved, and high under low-temperature melting conditions are achieved Mechanical properties.
Patent Information
- Application Number
- CN202410839330.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2024-06-26
- Publication Date
- 2024-12-31
AI Technical Summary
The mechanical strength of existing molding materials decreases under the molding history, especially low-temperature molten resins are prone to thermal decomposition, resulting in a decrease in the performance of composite materials.
Using molding materials containing cellulose fibers and resin, the resin contains polyester-based elastomer and high-polar polyester. The molecular weight distribution curve of the GPC method is optimized. The resin has a maximum value of 2 at a weight average molecular weight of more than 100,000. , and has a maximum value of 1 at a weight average molecular weight less than the maximum value of 2, and an area value at a maximum value of 2 is less than the area value of 1, combining a crosslinking agent and a flame retardant to improve mechanical strength.
Even in the presence of a molding heat history, the material's impact strength and bending elastic modulus are significantly improved and are suitable for the manufacture of molded products with high mechanical strength, such as containers and office equipment.
Smart Images

Figure HDA0004913993460000011 
Figure HDA0004913993460000021 
Figure HDA0004913993460000031
Abstract
Description
Technical Field
[0001] The present invention relates to a molding material. Background Art
[0002] In the past, molding materials containing cellulose fibers and resins are known. For example, Patent Document 1 discloses a cellulose composite resin containing cellulose fibers, a main resin such as an olefin resin, and a rubber-containing polymer. The rubber-containing polymer is composed of an aliphatic hydrocarbon or an aromatic hydrocarbon having only specific functional groups.
[0003] Patent Document 1: Japanese Patent Application Publication No. 2020-033541
[0004] However, the mechanical strength of the composite material of the prior art may be reduced in some cases when there is a molding heat history such as a case where the molded product or a gate material during molding is melted and pelletized and molded again. Summary of the invention
[0005] One aspect of the molding material according to the present invention is:
[0006] A molding material comprising cellulose fibers and resin,
[0007] The resin comprises a polyester elastomer and a high polar polyester,
[0008] In a molecular weight distribution curve obtained by GPC, the resin has a local maximum value 2 at a weight average molecular weight of 100,000 or more, and has a local maximum value 1 at a weight average molecular weight less than the local maximum value 2.
[0009] The area value at the maximum value 2 is smaller than the area value at the maximum value 1. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a figure (Table 1) which shows the composition of raw materials, the molding method and the evaluation results of the molded products concerning the molding materials of each Example and each Comparative Example.
[0011] Figure 2 It is a graph (Table 2) showing the composition of raw materials, the molding method, and the evaluation results of the molded products related to the molding materials of each Example and each Comparative Example.
[0012] Figure 3 It is a figure (Table 3) which shows the composition of the raw materials, the molding method and the evaluation results of the molded products concerning the molding materials of each Example and each Comparative Example. DETAILED DESCRIPTION
[0013] Hereinafter, the embodiments of the present invention will be described. The embodiments described below are the contents of examples for describing the present invention. The present invention is not subject to any limitation of the following embodiments, and also includes various variations implemented within the scope of not changing the gist of the present invention. It should be noted that all the configurations described below are not necessarily necessary configurations of the present invention.
[0014] 1. Molding materials
[0015] A molding material involved in one embodiment of the present invention is a molding material comprising cellulose fibers and a resin, wherein the resin comprises a polyester elastomer and a high-polarity polyester, and in a molecular weight distribution curve using a GPC method, the resin has a maximum value 2 at a weight average molecular weight of more than 100,000, and has a maximum value 1 at a weight average molecular weight less than the maximum value 2, and the area value at the maximum value 2 is smaller than the area value at the maximum value 1.
[0016] When there is a molding heat history such as melting and pelletizing the molded product or the gate material during molding, and then molding again, the various properties of the resin in the molding material deteriorate due to thermal decomposition. In particular, low-temperature melting resins that melt at a temperature below 200°C are prone to thermal decomposition.
[0017] Therefore, the present inventors have conducted intensive studies and have found that, when a resin has a moderately high molecular weight component, mechanical strengths such as Charpy impact strength and flexural modulus are excellent even in the presence of a molding heat history.
[0018] The molding material can be applied to a known molding method such as injection molding, press working, etc. The molded product made from the molding material is suitable for various containers, sheets, frames of office equipment such as printers, and home appliances as a substitute for polystyrene.
[0019] Hereinafter, various raw materials included in the molding material will be described.
[0020] 1.1 Cellulose fiber
[0021] The molding material according to the present embodiment includes cellulose fibers. The cellulose fibers function as a filler in a molded product and contribute to improving the expansion of the molding material and physical properties such as the strength of the molded product.
[0022] Cellulose fiber comes from plants and is a relatively abundant natural material. Therefore, compared with the use of synthetic fibers, the use of cellulose fibers promotes the reduction of environmental load. Cellulose fibers also have advantages in terms of the purchase or cost of raw materials. In addition, among various fibers, cellulose fibers have a high theoretical strength, which helps to improve the strength of molded products. As cellulose fibers, in addition to using raw pulp, old paper, old cloth, etc. can also be reused. In addition, commercial products can be used as cellulose fibers.
[0023] Cellulose fibers are mainly composed of cellulose, but may also contain components other than cellulose. Components other than cellulose include, for example, hemicellulose and lignin. In addition, cellulose fibers may be subjected to treatments such as bleaching.
[0024] From the viewpoint of improving the appearance of the molded article surface, the average fiber length of the cellulose fibers is preferably less than 500 μm, more preferably less than 50 μm. The average fiber length of the cellulose fibers is determined by a method in accordance with ISO 16065-2:2007.
[0025] The content of the cellulose fibers is preferably 9% by mass or more, more preferably 18% by mass or more, further preferably 27% by mass or more, further preferably 36% by mass or more, and particularly preferably 45% by mass or more relative to the total mass of the molding material. In addition, the content of the cellulose fibers is preferably 90% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less relative to the total mass of the molding material. When the content of the cellulose fibers is within the above range, good mechanical strength tends to be obtained even in the presence of a molding heat history.
[0026] 1.2 Resin
[0027] The molding material according to the present embodiment contains a resin, and the resin includes a polyester-based elastomer and a highly polar polyester.
[0028] Polyester elastomers act as a resin matrix to ensure the impact resistance (toughness) of the molded body. However, they have low compatibility with cellulose fibers, and the two are prone to interfacial peeling. Therefore, by using high-polarity polyester, which functions as a compatibilizer for cellulose fibers and polyester elastomers, interfacial peeling can be suppressed.
[0029] The content of the resin is preferably less than or equal to the content of the cellulose fibers described above. In this case, even in the presence of a molding heat history, a better mechanical strength tends to be obtained.
[0030] 1.2.1 Polyester elastomer
[0031] Polyester elastomers have thermoplasticity, and when molding materials are used to make molded products, they are melted to bond cellulose fibers to each other. In addition, polyester elastomers and cellulose fibers together bear the physical properties of the molded products. In particular, polyester elastomers enhance the toughness of molded products and improve impact strength. Furthermore, polyester elastomers have the possibility of being produced and used as bioplastics in the future, and are also expected to contribute to the reduction of environmental load.
[0032] The polyester elastomer preferably contains, as raw material monomers, an alkyl dicarboxylic acid or phthalic acid in which the carbon number of the alkylene group is 2 to 8 and an alkylene glycol in which the carbon number of the alkylene group is 2 to 8. When the polyester elastomer contains the above raw material monomers, better mechanical strength tends to be obtained even in the presence of a molding heat history.
[0033] The polyester elastomer is preferably obtained by copolymerizing the above two raw material monomers. It should be noted that the copolymerization can be carried out by a known synthesis method.
[0034] Examples of the alkyl dicarboxylic acid include straight-chain saturated aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and sebacic acid. These alkyl dicarboxylic acids may have a substituent in the molecular structure. Preferably, one or more of these are used in the synthesis of the polyester elastomer.
[0035] Phthalic acid may have a substituent in its molecular structure.
[0036] Examples of the alkylene glycol include diols such as 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, and 1,8-octanediol. It is preferred to use one or more of them in the synthesis of the polyester elastomer. The three raw material monomers are relatively easy to obtain and can be used for industrial or commercial purposes.
[0037] The polyester elastomer may contain other raw material monomers in addition to the above raw material monomers. As other raw material monomers, styrene, butadiene, acrylic acid, acrylate, methacrylic acid, methacrylate, acetonitrile, isobutylene, isoprene and ethylene can be cited, and one or more of them is preferably used. When such other raw material monomers are included, even in the presence of a molding heat history, better mechanical strength tends to be obtained.
[0038] When other raw material monomers are incorporated into the polyester elastomer, the total molar number of the other raw material monomers is preferably 1% or more and less than 50% of the total molar number of the raw material monomers. Thus, even in the presence of a molding heat history, better mechanical strength tends to be obtained.
[0039] The polyester elastomer may be a commercially available product. Examples of the commercially available product include ES-A60NX, E-D27N, E-D42N and ES series (these are trade names) of Anlon Chemical Co., Ltd. One or more of these may be used as the polyester elastomer.
[0040] Here, the presence or absence of the polyester-based elastomer in the form of the molding material or the molded product can be determined by the following physical property analysis and component analysis.
[0041] First, physical property analysis is performed to confirm whether there is a component with a complex elastic modulus of less than 100 MPa. When the above components are contained, it is determined to contain an elastomeric component. Specifically, for example, a scanning probe microscope NX20 from Park Systems Japan is used to measure the cross section of the molding material or the molded body in contact mode. Thus, the presence or absence of a component with a complex elastic modulus of 100 MPa can be confirmed. It should be noted that when confirming the presence or absence of an elastomeric component, a well-known nanoindenter can be used.
[0042] Next, qualitative analysis using both pyrolysis gas chromatography mass spectrometry (GC-MS) and Fourier transform infrared spectroscopy (FT-IR) is used to determine whether the elastomer component is a polyester elastomer. Pyrolysis GC-MS is an analysis method for identifying various fragments generated by thermal decomposition of a sample. FT-IR is an analysis method for identifying the molecular structure of a sample by the infrared absorption spectrum of the sample. The molecular structure of the sample can be determined by these.
[0043] The pyrolysis GC-MS method uses, for example, Frontier Lab's multi-shot pyrolysis instrument EGA / PY-3030D and Agilent Technologies' GC / MS 5975 equipped with the same. The FT-IR method uses, for example, Thermo Fisher Scientific's Nicolet (registered trademark) 380 Continu μm (registered trademark).
[0044] The content of the polyester elastomer is preferably 1% by mass or more, more preferably 5% by mass or more, and further preferably 10% by mass or more, relative to the total mass of the molding material. In addition, the content of the polyester elastomer is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less, relative to the total mass of the molding material. When the content of the polyester elastomer is within the above range, better mechanical strength tends to be obtained even in the presence of a molding heat history.
[0045] In addition, the content of the polyester elastomer is 25% by mass or more (more preferably 50% by mass or more, further preferably 75% by mass or more, and particularly preferably 100% by mass or more) relative to the content of the high polar polyester described below, and the total content of the polyester elastomer and the high polar polyester is preferably less than the content of the cellulose fiber described above. In this case, even in the presence of a molding heat history, better mechanical strength tends to be obtained.
[0046] In addition, the content of the polyester elastomer is preferably 400% by mass or less, more preferably 300% by mass or less, further preferably 250% by mass or less, and particularly preferably 200% by mass or less relative to the content of the high polar polyester described later. In such a case, even in the presence of a molding heat history, better mechanical strength tends to be obtained.
[0047] 1.2.2 High polar polyester
[0048] High polarity polyester improves the compatibility between cellulose fibers and polyester elastomers, thereby improving the wettability of the polyester elastomer with respect to cellulose fibers and mainly improving the flexural strength of the molded product.
[0049] The high polar polyester has a relatively high polar molecular structure, and preferably, in the repeating structure derived from the raw material monomer, the number of oxygen atoms is 1 or more relative to the number of carbon atoms being 2. In this case, even in the presence of a molding heat history, better mechanical strength tends to be obtained. Specifically, the high polar polyester preferably contains raw material monomers such as lactic acid, hydroxybutyric acid, malic acid, citric acid, malonic acid, succinic acid, serine, threonine, acrylic acid, methyl acrylate, and vinyl acetate as raw material monomers. These are relatively easy to obtain and can be used for industrial or commercial purposes.
[0050] Specifically, the high-polarity polyester preferably contains one or more polylactic acid, polyhydroxybutyric acid, polyacrylic acid, polymethyl acrylate and polyvinyl acetate. In addition, the high-polarity polyester can be a copolymer such as polyethylene succinic acid or P3HBH (3-hydroxy (butyrate-co-hexanoate)). Among these, the high-polarity polyester preferably contains one or more of polylactic acid and polyhydroxybutyric acid. Such a compound is biodegradable and can reduce environmental load. In addition, even in the presence of a molding heat history, it tends to obtain better mechanical strength. It should be noted that as a high-polarity polyester, a commercially available product can be used.
[0051] The content of the high polar polyester is preferably 1% by mass or more, more preferably 5% by mass or more, further preferably 10% by mass or more, particularly preferably 15% by mass or more, and more particularly preferably 20% by mass or more, relative to the total mass of the molding material. In addition, the content of the high polar polyester is preferably 90% by mass or less, more preferably 70% by mass or less, further preferably 50% by mass or less, and particularly preferably 40% by mass or less, relative to the total mass of the molding material. When the content of the high polar polyester is within the above range, better mechanical strength tends to be obtained even in the presence of molding heat history.
[0052] 1.2.3 Other resins
[0053] The resin contained in the molding material according to the present embodiment may contain resins other than polyester elastomers and high-polar polyesters. Examples of such resins include olefin resins such as polyethylene and polypropylene, polyurethane resins, and acrylic resins.
[0054] 1.2.4 Molecular weight distribution
[0055] In the molecular weight distribution curve obtained by the GPC method, the resin contained in the molding material according to the present embodiment has a local maximum 2 at a weight average molecular weight of 100,000 or more, and has a local maximum 1 at a weight average molecular weight less than the local maximum 2, and the area value at the local maximum 2 is smaller than the area value at the local maximum 1. In this way, since the resin has a moderately high molecular weight component, even if thermal decomposition of the resin occurs due to the molding heat history, the mechanical strength can be maintained.
[0056] GPC method refers to gel permeation chromatography, and can be measured, for example, by the following sequence. A device in which two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) are connected in series in a GPC device (ACQUITY APC, manufactured by Waters) is used as a measuring device. The measurement sample (molding material) is dissolved in chloroform as an eluent, and the molecular weight distribution curve of the resin is obtained by filtering with a filter having a pore size of 0.45 μm and performing GPC analysis on the dissolved component. Here, the column temperature is 40°C, and an IR detector is used as a detector. In addition, polystyrene (manufactured by Agilent) is used as a standard sample.
[0057] As a peak calculation method, for example, it can be performed as described below. The chromatogram is regarded as a linear function, and the position where the slope becomes 0 during differentiation is regarded as the peak top. The chromatogram is regarded as a linear function, and the position where the slope becomes 0 during differentiation is regarded as the peak boundary. The peaks are divided vertically starting from the peak boundary position, and the divided peaks are calculated as the area values of each peak. It should be noted that when the peaks are fully separated, the area value can be treated as a separate peak. In addition, when two overlapping mountains can be fully distinguished, they are treated as shoulder peaks, and the root of the small peak is drawn with a straight line to calculate the area value. Furthermore, the area of each peak can be calculated using peak separation software. However, the matching rate is above 90%.
[0058] In the molecular weight distribution curve by the GPC method, the resin contained in the molding material involved in the present embodiment has a local maximum value 2 at a weight average molecular weight of 100,000 or more, and the weight average molecular weight is preferably 110,000 or more, more preferably 120,000 or more, and further preferably 130,000 or more. In addition, it is preferred to have a local maximum value 2 at a weight average molecular weight of 500,000 or less, more preferably 400,000 or less, and further preferably 350,000 or less. When the local maximum value 2 is within the above range, even in the presence of a molding heat history, better mechanical strength tends to be obtained.
[0059] The resin contained in the molding material according to the present embodiment has a local maximum value 1 at a weight average molecular weight lower than the local maximum value 2 in the molecular weight distribution curve by the GPC method, preferably has a local maximum value 1 at a weight average molecular weight of 150,000 or less, more preferably has a local maximum value 1 at a weight average molecular weight of 120,000 or less, and further preferably has a local maximum value 1 at a weight average molecular weight of 100,000 or less. In addition, it is preferred to have a local maximum value 1 at a weight average molecular weight of 30,000 or more, further preferably has a local maximum value 1 at a weight average molecular weight of 50,000 or more, and particularly preferably has a local maximum value 1 at a weight average molecular weight of 60,000 or more. When the local maximum value 1 is within the above range, better mechanical strength tends to be obtained even in the presence of a molding heat history.
[0060] Here, (weight average molecular weight of maximum value 2) / (weight average molecular weight of maximum value 1) is preferably greater than 1.0 and less than 5.0, more preferably 1.1 or more and less than 4.0, further preferably 1.2 or more and less than 3.5, particularly preferably 1.5 or more and less than 3.0, and even more particularly preferably 1.6 or more and less than 2.5. In this case, even in the presence of a molding heat history, better mechanical strength tends to be obtained.
[0061] 1.3 Cross-linking agent
[0062] The molding material according to the present embodiment may further include a crosslinking agent. By including a crosslinking agent, it is easy to adjust the molecular weight distribution in the resin, and further, even in the case of a molding heat history, a better mechanical strength tends to be obtained.
[0063] As a crosslinking agent, it is preferred to have a reactive group capable of crosslinking with polyester. More specifically, the crosslinking agent preferably has a reactive group selected from a carbodiimide group, an amino group, an epoxy group, an isocyanate group, a protected isocyanate group, a carboxylic anhydride group, and a carboxyl group. A crosslinking agent having such a reactive group can preferably react with a polyester-based elastomer or a high-polarity polyester, and it is easy to adjust the molecular weight distribution in the resin, and thus, even in the presence of a molding heat history, it tends to obtain better mechanical strength.
[0064] As the crosslinking agent, commercially available products can be used, and examples thereof include Metablen P-1901 (manufactured by Mitsubishi Chemical Corporation), Dekonaal EX-321 (manufactured by Nagase ChemteX Corporation, trimethylolpropane triglycidyl ether), Dekonaal EX-211 (manufactured by Nagase ChemteX Corporation, neopentyl glycol diglycidyl ether), Duranate E402-B80B (Asahi Kasei Corporation, isocyanate), CARBODILITE HMV-5CA-LC (Nisshinbo Chemical Co., Ltd.), CARBODILITE Elastostab H01 (Nisshinbo Chemical Co., Ltd.), and Sigma-Aldrich: Product No. 188050 (Merck, poly(ethylene-alt-maleic anhydride)).
[0065] The content of the crosslinking agent is preferably 1% by mass or more, more preferably 2% by mass or more, relative to the total mass of the molding material. In addition, the content of the crosslinking agent is preferably 10% by mass or less, more preferably 8% by mass or less, and further preferably 6% by mass or less, relative to the total mass of the molding material. When the content of the crosslinking agent is within the above range, even in the presence of a molding heat history, better mechanical strength tends to be obtained.
[0066] In addition, when the total content of the resin is 100 parts by mass, the content of the crosslinking agent is preferably 3 parts by mass or more and 20 parts by mass or less, more preferably 5 parts by mass or more and 15 parts by mass or less, and particularly preferably 7 parts by mass or more and 13 parts by mass or less. When the content of the crosslinking agent is within the above range, even in the presence of a molding heat history, better mechanical strength tends to be obtained.
[0067] 1.4 Flame retardant
[0068] The molding material involved in this embodiment may also contain a flame retardant. The flame retardant may be a known substance. Examples of the flame retardant include inorganic flame retardants such as antimony compounds, metal hydroxides, nitrogen compounds, boron compounds, etc.; and organic flame retardants such as bromine compounds, phosphorus compounds, etc.
[0069] As the flame retardant, commercially available products may be used, and examples thereof include Rabitle FP-110 (manufactured by Mitsui Chemicals Fine Co., Ltd., a phosphazene-based flame retardant) and Exolit OP1230 (manufactured by Clariant, a phosphate-based flame retardant).
[0070] The content of the flame retardant is preferably 1% by mass or more and 15% by mass or less relative to the total mass of the molding material, more preferably 1% by mass or more and 10% by mass or less, and further preferably 3% by mass or more and 8% by mass or less. When the content of the flame retardant is within the above range, the flame retardancy of the molded product is improved, and even in the presence of a molding heat history, better mechanical strength tends to be obtained.
[0071] In addition, when the total content of cellulose fiber, polyester elastomer and high polar polyester is 100 parts by mass, the content of flame retardant is preferably 1 part by mass or more and 20 parts by mass or less, more preferably 5 parts by mass or more and 20 parts by mass or less, and further preferably 8 parts by mass or more and 15 parts by mass or less. When the content of flame retardant is within the above range, the flame retardancy of the molded article is improved, and even in the presence of molding heat history, better mechanical strength tends to be obtained.
[0072] 1.5 Other ingredients
[0073] The molding material according to the present embodiment may contain other components such as a colorant, an insect repellent, a mildew proof agent, an antioxidant, an ultraviolet absorber, a deflocculant, and a mold release agent.
[0074] 2. Manufacturing method of molding material
[0075] The method for producing the molding material will be described. A known method can be applied to the production of the molding material. Specifically, for example, the following method can be applied.
[0076] First, the raw materials are kneaded into a twisted strand using a single-screw kneading machine or a double-screw kneading machine, and then granulated to obtain a pelletized molding material.
[0077] In addition, the following method can be applied as a manufacturing method for molding materials. First, waste paper or pulp material is coarsely pulverized into cellulose fibers using a paper shredder. Then, the cellulose fibers, polyester elastomer and high-polarity polyester are measured and mixed. Next, the mixed raw materials are piled up in the air to form a sheet-like deposit. Since the deposit contains a large amount of air and has a low density, it is compressed using a calendering device to expel the air and increase the density. Next, after heating in a non-contact manner using a heating furnace, it is heated and stamped using a hot pressing device.
[0078] In the heating furnace and the hot press device, heating is preferably performed at a temperature higher than the melting temperature of the polyester elastomer and the high polar polyester by about 20° C. This tends to form a sheet in which each raw material is dispersed with suppressed unevenness.
[0079] Next, the sheet is cut into a desired shape using a shredder and used as a granular molding material. The desired shape of the molding material is not particularly limited, and is a roughly cubic shape from 2 mm cube to 5 mm cube. The molding material is manufactured by the above method. It should be noted that the manufacturing method of the molding material is not limited to the above method.
[0080] 3. Example
[0081] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0082] 3.1 Manufacturing of molding materials and test pieces
[0083] Figures 1 to 3 Tables 1 to 3 show the composition of raw materials, molding methods, and evaluation results of molded products related to the molding materials of each embodiment and each comparative example. Figures 1 to 3 In the columns of the compositions (Tables 1 to 3), the unit of the numerical value is parts by mass, and a column without a numerical value indicates that no component is contained.
[0084] right Figures 1 to 3 The following supplementary explanation is given for the loading of (Tables 1 to 3).
[0085] Polyester elastomer
[0086] · Product name ES-A60NX, ARON Chemical Co., Ltd.
[0087] Olefin elastomer
[0088] EPDM (ethylene propylene diene monomer rubber) (trade name: NOLDEL (registered trademark) 3720P, manufactured by Dow Toray Co., Ltd.)
[0089] High polar polyester
[0090] Polylactic acid (trade name Terramac (registered trademark) TE-2000, UNITIKA Corporation)
[0091] · Polyhydroxyalkane (P3HBH) (trade name: Green Planet (registered trademark), KANEKA Corporation)
[0092] Cellulose fiber
[0093] · Trade name: Guaiba BEKP, CMPC
[0094] Crosslinking agent
[0095] Cross-linking agent 1 (Metablen P-1901, manufactured by Mitsubishi Chemical Corporation)
[0096] Cross-linking agent 2 (Dekonaal EX-321, manufactured by Nagase ChemteX Co., Ltd., trimethylolpropane triglycidyl ether)
[0097] Cross-linking agent 3 (Dekonaal EX-211, manufactured by Nagase ChemteX Co., Ltd., neopentyl glycol diglycidyl ether)
[0098] Cross-linking agent 4 (Duranate E402-B80B, Asahi Kasei Corporation, isocyanate)
[0099] Cross-linking agent 5 (CARBODILITE HMV-5CA-LC, Nisshinbo Chemical Co., Ltd.)
[0100] Cross-linking agent 6 (CARBODILITE Elastostab H01, Nisshinbo Chemical Co., Ltd.)
[0101] Crosslinker 7 (Sigma-Aldrich: Product No. 188050, Merck, poly(ethylene-alt-maleic anhydride)
[0102] Flame retardants
[0103] Flame retardant 1 (Rabitle FP-110, manufactured by Mitsui Chemicals Fine Co., Ltd., phosphazene flame retardant)
[0104] Flame retardant 2 (Exolit OP1230, manufactured by Clariant, phosphate flame retardant)
[0105] according to Figures 1 to 3 The molding materials according to the examples and comparative examples were prepared according to the compositions of Tables 1 to 3. Specifically, polyester elastomer, high polar polyester, olefin elastomer as other elastomer, cellulose fiber, crosslinking agent, etc. were weighed.
[0106] Then, it was put into Technobel's twin-shaft kneading machine KZW15TW-45MG for kneading. The kneading conditions were a maximum heating temperature of 180°C and an extrusion output of 1 kg / hr. Then, after being processed into a twisted wire shape, it was made into a granular molding material using a granulator.
[0107] The weight average molecular weight of the molding material obtained above was measured by GPC method. Specifically, a device in which two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) are connected in series in a GPC device (ACQUITY APC, manufactured by Waters) is used as a measuring device. The measurement sample (molding material) is dissolved in chloroform as an eluent, and the molecular weight distribution curve of the resin is obtained by filtering with a filter having a pore size of 0.45 μm and performing GPC analysis on the dissolved component. Here, the column temperature is 40°C, the detector uses an IR detector, and polystyrene (manufactured by Agilent) is used as a standard sample. As a peak calculation method, it is carried out as described above.
[0108] The molding materials involved in each embodiment and each comparative example were used to perform molding by injection molding or stamping. Specifically, the heating temperature of the molding materials for injection molding and stamping was 200° C. THX40-5V of Nissei Plastic Industry Co., Ltd. was used as an injection molding device, and PHKS-40ABS of Towa Seiki Co., Ltd. was used as a stamping device.
[0109] Here, in Figures 1 to 3 In the molding history of (Tables 1 to 3), "re-pelletizing once" means that the product that has undergone the above molding process is re-pelletized and the molding process is performed again in the same manner as above, and "first time" means that the molding process is performed only once for the first time without re-pelletizing. Figures 1 to 3 In the crosslinking agent adding step of (Tables 1 to 3), "re-pelletization" means adding when the product subjected to the above molding process is re-pelletized, and "first time" means adding only when the raw materials are kneaded. In this way, test pieces in each example and each comparative example were obtained.
[0110] 3.2 Evaluation test
[0111] As an indicator of impact strength, Charpy impact strength was used, and the test method was implemented in accordance with ISO 179 (JIS K7111). The shape of the test piece was a rectangular plate with a long side of 80 mm ± 2 mm, a short side of 4.0 mm ± 0.2 mm, and a thickness of 10.0 mm ± 0.2 mm. The test device used was an impact tester IT of Toyo Seiki Seisaku-sho Co., Ltd. In the Charpy impact test, the hammer weight was 4 J (WR 2.14 N / m), the lifting angle was 150°, the notch remaining width was 8.0 mm ± 0.2 mm, and the notch angle was 45°.
[0112] Bending properties were used as an indicator of bending strength, and the test method was implemented in accordance with ISO 178 (JIS K7171). The shape of the test piece was a rectangular plate with a long side of 80 mm ± 2 mm, a short side of 10.0 mm ± 0.2 mm, and a thickness of 4.0 mm ± 0.2 mm. The test device used was Instron's 68TM-30, and the test was performed with the fulcrum spacing set to 64 mm.
[0113] With respect to the test results obtained for each level, the strength of the molded product was determined based on the following criteria.
[0114] Judgment Criteria
[0115] A: Charpy impact strength is 7kJ / m 2 The bending modulus is 3000 MPa or more.
[0116] B: Charpy impact strength is 4 kJ / m 2 and the flexural modulus is 1500 MPa or more (but excluding the range of A judgment).
[0117] C: Charpy impact strength is 4 kJ / m 2 or above, or the flexural modulus is 1500 MPa or above (but excluding the ranges of A and B judgments).
[0118] D: Charpy impact strength is 4 kJ / m 2 The flexural modulus is 1500 MPa or less (except for the ranges of B and C).
[0119] E: Cannot be formed.
[0120] 3.3 Evaluation results
[0121] The evaluation results are shown in Figures 1 to 3 (Tables 1 to 3).
[0122] Depend on Figures 1 to 3 From the results shown in (Tables 1 to 3), it can be seen that a molding material comprises cellulose fibers and a resin, wherein the resin comprises a polyester elastomer and a high-polarity polyester, and in a molecular weight distribution curve using a GPC method, the resin has a local maximum 2 at a weight average molecular weight of 100,000 or more, and has a local maximum 1 at a weight average molecular weight less than the local maximum 2, and the area value at the local maximum 2 is smaller than the area value at the local maximum 1, and the molding material involved in each embodiment obtains good mechanical strength even in the presence of a molding heat history.
[0123] On the other hand, the molding material according to the comparative example that does not satisfy the above-mentioned configuration does not obtain good mechanical strength when there is a molding heat history.
[0124] The following contents are derived from the above-mentioned implementation modes.
[0125] In one embodiment of the molding material,
[0126] A molding material comprising cellulose fibers and resin,
[0127] The resin comprises a polyester elastomer and a high polar polyester,
[0128] In a molecular weight distribution curve obtained by GPC, the resin has a local maximum value 2 at a weight average molecular weight of 100,000 or more, and has a local maximum value 1 at a weight average molecular weight less than the local maximum value 2.
[0129] The area value at the maximum value 2 is smaller than the area value at the maximum value 1.
[0130] In one embodiment of the above-mentioned molding material,
[0131] The molding material may further contain a cross-linking agent.
[0132] In any of the above-mentioned molding materials,
[0133] The crosslinking agent may have a reactive group selected from a carbodiimide group, an amino group, an epoxy group, an isocyanate group, a protected isocyanate group, a carboxylic anhydride group, and a carboxyl group.
[0134] In any of the above-mentioned molding materials,
[0135] The content of the polyester elastomer is 25% by mass or more relative to the content of the high-polarity polyester.
[0136] The total content of the polyester elastomer and the high-polar polyester may be less than the content of the cellulose fiber.
[0137] In any of the above-mentioned molding materials,
[0138] The content of the polyester-based elastomer may be 400% by mass or less relative to the content of the high-polar polyester.
[0139] In any of the above-mentioned molding materials,
[0140] The polyester-based elastomer may contain, as raw material monomers, an alkyl dicarboxylic acid or phthalic acid in which the alkylene group has 2 to 8 carbon atoms and an alkylene glycol in which the alkylene group has 2 to 8 carbon atoms.
[0141] In any of the above-mentioned molding materials,
[0142] The polyester elastomer further comprises other raw material monomers in addition to the raw material monomers.
[0143] The other raw material monomers may be one or more of styrene, butadiene, acrylic acid, acrylic ester, methacrylic acid, methacrylic ester, acetonitrile, isobutylene, isoprene, and ethylene.
[0144] In any of the above-mentioned molding materials,
[0145] The highly polar polyester may have 1 or more oxygen atoms relative to 2 carbon atoms in a repeating structure derived from a raw material monomer.
[0146] In any of the above-mentioned molding materials,
[0147] The high polar polyester may include one or more of polylactic acid and polyhydroxybutyric acid.
[0148] In any of the above-mentioned molding materials,
[0149] The average fiber length of the cellulose fibers may be less than 500 μm.
[0150] The present invention is not limited to the above-mentioned embodiments, and various modifications are possible. For example, the present invention includes a configuration substantially the same as the configuration described in the embodiments, such as a configuration having the same function, method and result, or a configuration having the same purpose and effect. In addition, the present invention includes a configuration that replaces a non-essential part of the configuration described in the embodiments. In addition, the present invention includes a configuration that has the same effect as the configuration described in the embodiments, or a configuration that achieves the same purpose. In addition, the present invention includes a configuration in which a known technology is added to the configuration described in the embodiments.
Claims
1. A molding material, characterized in that: Contains cellulose fibers and resins, The resin comprises a polyester elastomer and a high polar polyester, In a molecular weight distribution curve obtained by GPC, the resin has a local maximum value 2 at a weight average molecular weight of 100,000 or more, and has a local maximum value 1 at a weight average molecular weight less than the local maximum value 2. The area value at the maximum value 2 is smaller than the area value at the maximum value 1.
2. The molding material according to claim 1, wherein The molding material further includes a cross-linking agent.
3. The molding material according to claim 2, wherein The crosslinking agent has a reactive group selected from a carbodiimide group, an amino group, an epoxy group, an isocyanate group, a protected isocyanate group, a carboxylic anhydride group, and a carboxyl group.
4. The molding material according to claim 1 or claim 2, wherein: The content of the polyester elastomer is 25% by mass or more relative to the content of the high-polarity polyester. The total content of the polyester elastomer and the high-polar polyester is less than the content of the cellulose fiber.
5. The molding material according to claim 1 or claim 2, wherein: The content of the polyester-based elastomer is 400% by mass or less relative to the content of the high-polar polyester.
6. The molding material according to claim 1 or claim 2, wherein: The polyester elastomer contains, as raw material monomers, an alkyl dicarboxylic acid or phthalic acid in which the alkylene group has 2 to 8 carbon atoms and an alkylene glycol in which the alkylene group has 2 to 8 carbon atoms.
7. The molding material according to claim 6, wherein The polyester elastomer contains other raw material monomers in addition to the raw material monomers, and the other raw material monomers are one or more of styrene, butadiene, acrylic acid, acrylic acid ester, methacrylic acid, methacrylic acid ester, acetonitrile, isobutylene, isoprene, and ethylene.
8. The molding material according to claim 1 or claim 2, wherein: The highly polar polyester has a repeating structure derived from a raw material monomer in which the number of carbon atoms is 2 and the number of oxygen atoms is 1 or more.
9. The molding material according to claim 1 or claim 2, wherein: The high polar polyester includes one or more of polylactic acid and polyhydroxybutyric acid.
10. The molding material according to claim 1 or claim 2, wherein: The average fiber length of the cellulose fibers is less than 500 μm.